U.S. policy toward China under the administration of Donald Trump - Nataliia Gorodnia (Американська історія і політика, 2021)
This paper intends to describe and discuss the major shifts in the U.S. policy toward China under the administration of Donald Trump. Methodology. The research is based on historical methods, including a chronological approach, a study of primary sources and a comparative analysis. The developments in the U.S. policy are considered at the background of new strategic approaches and their implementation on the bilateral and regional levels.